Cost-Effectiveness of CT Perfusion for Selecting Patients for Intravenous Thrombolysis: A US Hospital Perspective - Jackson, D.; Earnshaw, S.R.; Farkouh, R.; Schwamm, L. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Improved selection of patients with stroke for IV tPA treatment may enhance clinical outcomes. Given the limited availability of MR imaging in hospitals, we examined the cost-effectiveness of adding CTP to the usual CT-based methods for selecting patients on the basis of the presence and extent of penumbra. MATERIALS AND METHODS: A decision-analytic model estimated the costs and outcomes associated with penumbra-based CTP selection in a patient population similar to that enrolled in the IV tPA clinical trials. Model inputs were obtained from published literature, clinical trial data, standard US costing sources, and expert opinion. Cost per life-year saved and cost per QALY gained were estimated from a hospital perspective. RESULTS: Addition of penumbra-based CTP to standard unenhanced CT improved favorable outcome (mRS, ≤1) by 0.59% and reduced cost by $42 compared with selection based on unenhanced CT alone. Life-years and QALYs improved. Multivariate sensitivity analysis predicted cost-effectiveness (≤$50,000 per QALY) in 89.2% of simulation runs. CONCLUSIONS: Using penumbra-based CTP after routine CT to select patients with ischemic stroke for IV tPA is cost-effective compared with the usual CT-based methods for hospitals. With the ease of access of CTP, penumbra-based selection methods may be readily available to hospitals. Thus, this economic analysis may lend further support to the consideration of a paradigm shift in acute stroke evaluation. CIconfidence intervalCTPperfusion CTDWIdiffusion-weighted imagingECASSEuropean Cooperative Acute Stroke StudyEDemergency departmentFDAUS Food and Drug AdministrationHrshoursICD-9international classification of diseases, 9th revisionICHintracranial hemorrhageIVintravenousIV tPAintervenous tissue plasminogen activatormRSmodified Rankin ScalePWIperfusion-weighted imagingQALYquality-adjusted life-yearSAHsubarachnoid hemorrhageSICHsymptomatic intracerebral hemorrhage